PHYTOPHARMACOLOGICAL EVALUATION OF SOLANUM SURATTENSE BURN: USED IN FOLK MEDICINES OF CHOLISTAN DESERT PAKISTAN - SOFIA ERAM,; MAHMOOD AHMAD,; SHAFIA ARSHAD, (International Journal of Pharma and Bio Sciences, 2013)
Ethanolic extracts of aerial parts of Solanum surattense burn. (SS), were subjected to in vivo study, by means of serum biochemical parameters and histopathological observations, in order to verify its traditional use in Hepatobiliary disorders. All groups of rabbits received a single dose of CCl4 subcutaneously on 7th day except group I which was served as normal control . Group II served as CCl4 control. While groups III, IV and V were served as silymarin control , test group 1 and test group 2 respectively. Results showed that CCl4 control group had raised levels of SGOT, SGPT and ALP significantly but TB level was not raised as compared to a normal control group. Pre-treatment with SS extract showed hepatoprotection as obvious by significant reinstatement of levels of SGOT, SGPT and ALP, while TB level was not changed significantly when compared with CCl4 control group. SS extract was more effective as compared to both silymarin and SS extracts because SS extract only significantly reduced SGOT level but unable to restore SGPT, ALP and TB levels. Histopathological examination of the liver tissue was further corroborated these results. Thus the outcome of the present study supports the conventional believes on hepatoprotective effects of Solanum surattense .